2021
DOI: 10.1016/j.trsl.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

TMAO: how gut microbiota contributes to heart failure

Abstract: An increasing amount of evidence reveals that the gut microbiota is involved in the pathogenesis and progression of various cardiovascular diseases. In patients with heart failure (HF), splanchnic hypoperfusion causes ischemia and intestinal edema, allowing bacterial translocation and bacterial metabolites to enter the blood circulation via an impaired intestinal barrier. This results in local and systemic inflammatory responses. Gut microbe-derived metabolites are implicated in the pathology of multiple disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 150 publications
(163 reference statements)
3
94
0
Order By: Relevance
“…Whether high TMAO levels are a cause or result of poor prognosis of HF is controversial, 9 but, in the present study, we confirmed that high TMAO was associated with poor prognosis independent of established prognostic indicators such as previous hospitalization for HF, renal dysfunction, and anaemia. In addition, even if B‐type natriuretic peptide and nutritional indicators, BMI and GNRI, were included in the propensity score, high TMAO still remained to be associated with poor prognosis ( P < 0.05) (data not shown).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Whether high TMAO levels are a cause or result of poor prognosis of HF is controversial, 9 but, in the present study, we confirmed that high TMAO was associated with poor prognosis independent of established prognostic indicators such as previous hospitalization for HF, renal dysfunction, and anaemia. In addition, even if B‐type natriuretic peptide and nutritional indicators, BMI and GNRI, were included in the propensity score, high TMAO still remained to be associated with poor prognosis ( P < 0.05) (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…This promotes atherosclerosis and is associated with increased morbidity and mortality in coronary artery disease 10,12,13 . TMAO also directly affects the heart by inducing myocardial hypertrophy and fibrosis, 14 inflammation, 15 and mitochondrial dysfunction of the myocardium, 16 which may affect development and prognosis of HF 9 . The association between TMAO and prognosis has been investigated in patients with HF with reduced ejection fraction (HFrEF) 6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…TMAO is then transported to tissues or excreted into the urine. TMAO acts atherogenic [120][121][122][123][124]. Updated systematic review and meta-analysis indicate that TMAO increased the hazard ratio (HR) of CHD mortality [125].…”
Section: Debates Around Trimethylamine Oxide (Tmao)mentioning
confidence: 99%
“…Moreover, gut dysbiosis has also been linked to psoriasis and its comorbidities [33]. One of the current hypotheses for the pathophysiological mechanism linking alteration in gut microbiome with increased cardiovascular risk states that the bacterial metabolites are translocated via impaired gut barrier into the circulation and exert systemic effects [14]. Several studies confirmed intestinal barrier damage in psoriasis [16][17][18] as well as increased blood concentration of bacterial components (lipopolysaccharide, DNA) in psoriatic patients [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma TMAO is a metabolite derived from dietary precursors (choline, phosphatidylcholine, and L-carnitine), through the activity of gut microbiota [10]. Several studies have revealed a relation between plasma TMAO concentration and cardiovascular diseases, such as myocardial infarction, chronic heart failure, atrial fibrillation, or stroke [11][12][13][14]. Fecal microbial transplantation in a murine model demonstrated the role of intestinal microbiota in transmission of atherosclerosis susceptibility and overall TMAO production [15].…”
Section: Introductionmentioning
confidence: 99%